Development of an Islamic context-based module to improve mathematical problem-solving ability - Isna Ilviatun Naela; Fitria Zana Kumala (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
Mathematical problem-solving abilities are a crucial part of the mathematics curriculum, necessary for solving real-life problems. The mathematical problem-solving abilities of students at Bustanul Ulum Paguyangan Middle School remain low, as the learning approach is conventional and the teaching materials are limited to textbooks. This research aims to develop an Islamic context-based module on circular material that is both valid and effective in improving the mathematical problem-solving abilities of class VIII students at Bustanul Ulum Paguyangan Middle School. The type of research is Research and Development (R&D). The results indicate that the Islamic context-based module is valid according to the material expert validation and Islamic context, which received a score of 85.41%, media expert validation at 80%, mathematics teacher trials at 81.67%, small group trials at 83.28%, and field trials at 81.71%. Furthermore, the module was found to be effective in improving students' mathematical problem-solving abilities, with an average N-Gain score for the experimental class of 0.80 (high category), better than the control class's average N-Gain score of 0.40 (medium category). Based on these results, a t-test for two independent samples resulted in a value of 0.00, which is smaller than the significance level of 0.05. Therefore,  is rejected and  is accepted, indicating that the Islamic context-based module is valid based on material and media expert tests, teacher trials, small group trials, and field trials, and is effective in improving the mathematical problem-solving abilities of class VIII students at Bustanul Ulum Paguyangan Middle School.